Sistem Carnet dalam Penyelesaian Impor Barang Sementara di Kantor Bea Cukai - Hanifah Hanifah; Aditya Rizky Azhari; Andri Primadi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The General Directorate of Customs is an agency assigned by the government to regulate goods entering and leaving the country, and Customs has customs facilities, namely temporary import and recently customs clearance together with KADIN and IMI makes temporary import easier with carnet system. The problem in this study is the role of the carnet system in the completion of the temporary import goods in the main service office of the Soekarno Hatta Customs Office. The purpose of this study is to determine the role of the carnet system in the settlement of temporary import goods. To solve the problem of the author used 2 methods, first the method of collecting data in the form of field data and literature data. The second method of descriptive qualitative analysis is the analysis used to analyze and observe social situations broadly, thoroughly and deeply. The results of the analysis and discussion of carnet are documents used for temporary import with a period of 12 months. In the carnet there is the ATA carnet (Admission Temporary/ Temporary Admission Carnet) and CPD carnet (Carnet de Passages en Duane). There is a procedure for obtaining approval of temporary import facilities, terms and conditions for temporary import and sanctions. The procedure for using the carnet is that the importer reports to the general directorate of customs or the head of the customs service office and pays a guarantee until the completion of the temporary import by the carnet. There are the relevant agencies dealing with carnet KADIN (Indonesian Chamber of Commerce and Industry) and IMI (Indonesian Motor Association) as well as the advantages and role of carnet in the temporary import settlement. The advantage of using this carnet system is that it is very fast in checking the release of goods because it only uses carnet document for each item.